Comparison of outcomes after vaginal reconstruction surgery between elderly and younger women - Yiap Loong Tan; Tsia-Shu Lo; Siwatchaya Khanuengkitkong; Anil Krishna Dass (Elsevier, 2014)
Objective: The objective of this study was to estimate the association of vaginal sacrospinous ligament fixation with anterior-transobturator mesh repair surgery for advanced pelvic organ prolapse in patients of two different age groups. Materials and methods: Vaginal sacrospinous ligament fixation with anterior mesh repair as primary prolapse surgery was performed on 225 patients with advanced pelvic organ prolapse (POP-Q ≥ stage III). POP-Q < stage II was objective cure and subjective cure was determined according to feedback of POPDI-6 (Questions 2 and 3). Patients provided responses to UDI-6, IIQ-7, POPDI-6, and PISQ-12 pre- and postsurgery. Outcome measures were observed in cohorts of two age groups (<75 years and ≥75 years). Results: Postoperative data of 217 patients were available. The cumulative objective cure rates were 93.0% and 92.5% for patients aged ≥75 years and <75 years, respectively, with mean follow-up of 33.93 ± 18.52 months and 36.44 ± 19.34 months respectively. The UDI-6, IIQ-7, POPDI-6, and PISQ-12 scores within each of the two age groups improved significantly after surgery. Comparatively, the POPDI-6 score was better whereas the PISQ-12 score was poorer among patients aged ≥75 years. Older women had significantly more preoperative comorbidities. The operative time, perioperative complications, and length of hospital stay showed no difference between the two groups. The intraoperative blood loss was significantly less in the older group and neither group had mortality. Conclusion: This study showed that adequately optimized older patients undergoing pelvic organ prolapse surgery experienced the same anatomical outcomes, comparable improved quality of life, morbidity, and mortality as their counterparts of younger age.